2006
DOI: 10.1101/lm.316006
|View full text |Cite
|
Sign up to set email alerts
|

Development switch in neural circuitry underlying odor-malaise learning

Abstract: Fetal and infant rats can learn to avoid odors paired with illness before development of brain areas supporting this learning in adults, suggesting an alternate learning circuit. Here we begin to document the transition from the infant to adult neural circuit underlying odor-malaise avoidance learning using LiCl (0.3 M; 1% of body weight, ip) and a 30-min peppermint-odor exposure. Conditioning groups included: Paired odor-LiCl, Paired odor-LiCl-Nursing, LiCl, and odor-saline. Results showed that Paired LiCl-od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 165 publications
(186 reference statements)
2
48
0
Order By: Relevance
“…They show that conditioning induces an odor aversion in P7, P12, and P23 pups and that the aversion is independent of amygdala in P7 and P12 pups, but implicates it in P23 pups. The neural circuit supporting the same learned behavior may be different in the pup and the weanling rat (Shionoya et al 2006). Such a change in the substrates of learning may involve differences in memory processing and modify its duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They show that conditioning induces an odor aversion in P7, P12, and P23 pups and that the aversion is independent of amygdala in P7 and P12 pups, but implicates it in P23 pups. The neural circuit supporting the same learned behavior may be different in the pup and the weanling rat (Shionoya et al 2006). Such a change in the substrates of learning may involve differences in memory processing and modify its duration.…”
Section: Discussionmentioning
confidence: 99%
“…Research on cognitive development has demonstrated very early learning capacities in vertebrates; different kinds of associative learning may be acquired by neonates and even by the fetus (Smotherman et al 1982;Kehoe and Blass 1986;Cheslock et al 2000;Sullivan 2001;Smotherman 2002;Gruest et al 2004a;Shionoya et al 2006). Some of these early acquisitions have been shown to be retained in the long term, but the characteristics of long-term memory in the course of development are still poorly known, particularly concerning its stabilization.…”
mentioning
confidence: 99%
“…At P12-13, the three conditions induce odor avoidance, but the basolateral complex of the amygdala is activated only when the odor is paired with a 0.5-mA shock but not when a stronger, 1.2-mA shock or LiCl injection is administered. In contrast, at P23-24, the basolateral complex is activated under all three conditions (Raineki et al, 2009;Shionoya et al, 2006). Similarly, at P14, exposure to a male rat induces c-fos expression in the medial nucleus of the amygdala, but not in the lateral nucleus, whereas, at P18, c-fos expression is observed in both the medial and the lateral nuclei (Chen et al, 2006;but see Wiedenmayer and Barr, 2001a).…”
Section: Functional Considerationsmentioning
confidence: 96%
“…For example, at P7-8, a 0.5-mA or a 1.2-mA shock or LiCl injection induces odor preference or avoidance without activation of the basolateral complex of the amygdala as revealed by 2-deoxyglucose uptake (Raineki et al, 2009;Shionoya et al, 2006). At P12-13, the three conditions induce odor avoidance, but the basolateral complex of the amygdala is activated only when the odor is paired with a 0.5-mA shock but not when a stronger, 1.2-mA shock or LiCl injection is administered.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…At weaning (PN23-24), all learning paradigms produced learning-associated changes in the posterior piriform cortex and basolateral amygdala complex. These results suggest at least two basic principles of the development of the neurobiology of learning: (1) Learning that appears similar throughout development can be supported by neural systems showing very robust developmental changes, and (2) the emergence of amygdala function depends on the learning protocol and reinforcement condition being assessed.Even in utero, infant rats rapidly learn to avoid odors paired with malaise (LiCl) as expressed by learning an odor aversion (Garcia et al 1966(Garcia et al , 1974Hennessey et al 1976;Haroutunian and Campbell 1979;Smotherman 1982;Stickrod et al 1982;Rudy and Cheatle 1983;Kucharski and Spear 1984;Smotherman and Robinson 1985, 1990;Alleva and Calamandrei 1986;Miller et al 1990b; Best 1992, 1993;Richardson and McNally 2003;Gruest et al 2004;Shionoya et al 2006). In contrast to adult odor-LiCl learning, which relies on the amygdala (Touzani and Sclafani 2005), this early-life, odoraversion learning relies on the olfactory bulb until the pup approaches weaning age, when the amygdala is incorporated into the learning circuitry (Shionoya et al 2006).…”
mentioning
confidence: 99%